Translating a post industrial landscape: The rebirth of Pukewā - Hoffmann, Karl; Southcombe, Mark (Interstices: Journal of Architecture and Related Arts, 2022)
This research investigation explores how, through the use of architectural narrative informed by translation theory, the built environment can be conceived and imagined as a vessel linking the past with the present and future, in turn solidifying a stronger sense of place-duration within human settlements. The project argues that by consolidating these links in post-industrial sites, visitors and residents can be better equipped to understand their unique contexts while being provided with stronger forms of place-engagement for surviving communities.The township of Waihi, at the base of the Coromandel Peninsula, has a mining history spanning three centuries. Here, the land has been inexorably violated in the search for gold and silver. Mining operations are planned to continue through until 2035 when the landscape, exhausted of extractable mineral worth, will then begin a stage of rehabilitation. This design-led investigation envisages Waihi and its post-industrial potential at this point. The research proposes an axial intervention spanning mine, town and adjacent maunga or mountain, on which are threaded and counterposed various architecture ‘moments’ that speak to diverse temporalities and narrative histories. These rehabilitation efforts anticipate an ‘afterlife’ capable of emerging from, and in key ways overcoming, the scars and truncated memories accruing in this place. The result imagines an architecture where stories of the changing landscape can sustain long into the future.